Vulnerability of the clinical method - José Carlos Hernández Aragonés (Medisur)
This article is aimed at outlining the general aspects that undermine the use of the clinical method in everyday medical practice and also at exposing those that cause a negative effect on the use of the various steps leading to the correct diagnosis and treatment of a patient. A presentation is made on the issues and situations that may contribute not to take into account the clinical method and the requirements for its implementation. Finally, it is concluded that the importance and appropriate management of the clinical method is not still widely known and that the decline of the doctor-patient relationship is a key element that hinders its application.